Shaping the future of primary healthcare: Factors influencing medical students’ preference for family medicine specialty in Qatar - Maryam A. Al-Rashid; Muna T Abed Alah; Areej S. Al-Hamad; Michail Nomikos; Marwan F. Abu Hijleh (Journal of Family and Community Medicine)
BACKGROUND: As countries strive to strengthen primary healthcare systems, understanding medical students’ specialty preferences, particularly for Family Medicine, becomes crucial. Objective of present study was to determine factors that influence medical students’ preferences for Family Medicine in Qatar. MATERIALS AND METHODS: A study was conducted among medical students at one public university in Qatar from March 1, 2023, to March 15, 2023. Data collected using a structured, validated questionnaire; students participated in the study by filling an online questionnaire. Information sought included sociodemographic characteristics, medical specialty preferences, and the impact of 31 factors on these choices such as interest in dealing with diverse patient issues, and the influence of physician role models among others. Statistical analysis performed using SPSS version 26.0 Descriptive statistics, including frequencies and percentages, were used to summarize participant demographics and medical specialty preferences. Mann–Whitney U-test tested the difference in preference for family medicine specialty by various students’ characteristics. Logistic regression analysis performed to identify factors related to preferring Family Medicine. RESULTS: A total of 262 students completed the survey with age ranging between 17-24 years (Mean=20, SD=1.7 years); majority (68.3%) were females and 54.4% were non-Qatari. About 16% students reported having a first degree relative or a family friend with family medicine specialty. Compared to surgery and internal medicine, a fewer students selected family medicine as their preferred specialty. Surgery was ranked as the top career choice (53.4%) followed by internal medicine (36.5%) and pediatrics (31.7%). Presence of a personal connection to a field seemed to have a significant impact on student preference. Being in the clerkship phase of medical education (adjusted odds ratio [AOR]=2.18, 95% CI: 1.12–4.23, P = 0.022) and possessing a personal connection to Family Medicine (AOR= 3.46, 95% CI: 1.65–7.29, P = 0.001) significantly predicted the selection of Family Medicine between students’ top two choices. CONCLUSION: Clinical exposure and personal connections influence students’ preference for family medicine specialty. Promoting these elements through targeted educational and mentorship programs may increase students’ interest in Family Medicine and help to address the gap between student preferences and the greater need for primary care providers.